Analisis Pengaruh Struktur, Prosedur dan Strategi Organisasi dalam Reformasi Perpajakan terhadap Kepatuhan Wajib Pajak - LISTYA SUGIYARTI (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2017)
This research is an activity to know the factors that influence tax payer compliance in compliance to pay tax. The purpose of research is to examine and analyze the amount of research variables as follows: (1) Conditions: organizational structure, organizational procedures and organizational strategy in the tax reform dimension. (2) Conditions of taxpayer compliance. (3) How big influence: organizational structure, organizational procedure and organizational strategy to taxpayer compliance partially. (4) How much influence: organizational structure, organizational procedure and organizational strategy to tax payer compliance simultaneously. This quantitative research is described in descriptive and verification analysis and conducted in Pratama Kramat Jati Jakarta by taking 100 samples from the taxpayer. Sample determination technique in this research is taken by Random Sampling. Data analysis method used to test this quantitative research hypothesis is lane analysis. The results showed that respondents: (1) Conditions of organizational structure, organizational procedures and organizational strategy is quite good up to well. (2) The condition of taxpayer compliance is quite good up to well. (3) There is a positive and significant influence of organizational structure, organizational procedure and organizational strategy to partial tax compliance. (4) There is significant influence from organizational structure, organizational procedure and organizational strategy to taxpayer compliance simultaneously.